2019
DOI: 10.1093/jac/dkz082
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a pharmacist-led penicillin allergy de-labelling ward round: a novel antimicrobial stewardship intervention

Abstract: Background: Antibiotic allergy labels (AALs), reported by up to 25% of hospitalized patients, are a significant barrier to appropriate prescribing and a focus of antimicrobial stewardship (AMS) programmes.Methods: A prospective audit of a pharmacist-led AMS penicillin allergy de-labelling ward round at Austin Health (Melbourne, Australia) was evaluated. Eligible inpatients with a documented penicillin allergy receiving an antibiotic were identified via an electronic medical report and then reviewed by a pharma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 19 publications
3
60
0
1
Order By: Relevance
“…These patients would not have been identified through our inclusion criteria search as the BL allergy would no longer be listed on their profile. Recent studies have reported positive effects of BL allergy de‐labeling including decreased use of NPAs and increased utilization of BLs . During the development of our BPA, removing allergies that were deemed intolerances or nonsignificant allergies was discussed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These patients would not have been identified through our inclusion criteria search as the BL allergy would no longer be listed on their profile. Recent studies have reported positive effects of BL allergy de‐labeling including decreased use of NPAs and increased utilization of BLs . During the development of our BPA, removing allergies that were deemed intolerances or nonsignificant allergies was discussed.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported positive effects of BL allergy de- labeling including decreased use of NPAs and increased utilization of BLs. [19][20][21] During the development of our BPA, removing allergies that were deemed intolerances or nonsignificant allergies was discussed.…”
Section: Discussionmentioning
confidence: 99%
“…5,9,33 Paper and computer-based stratification tools have been developed and employed at various stages of the patient's journey by clinicians and pharmacists in hospitalised patients and for preoperative testing. 5,[34][35][36][37] Application of these tools results in 1 of 3 possible outcomes: removal of spurious PenA label; referral to specialist allergy assessment services for those deemed to be high risk; or confirmation of PenA status.…”
Section: Pena Delabelling Methodsmentioning
confidence: 99%
“…Recent studies of newer approaches of direct PenA delabelling using structured review and algorithms have primarily focussed on safety and clinical effectiveness (see Table ). Those conducted in hospital settings have involved a multidisciplinary team as a part of AMS programmes; and outpatient delabelling has mainly involved allergy specialist clinics . Patient partnership is key to the success of direct Pen‐A delabelling, however, some patients do not consent to participate and even when they do, are not comfortable with re‐exposure …”
Section: Introductionmentioning
confidence: 99%
“…It has subsequently been used by hospital pharmacists and nurses to assess betalactam allergy labels. 35 This tool classifies penicillin allergies into colour-coded risk groups and suggests an appropriate method for de-labelling: 34,36 • no risk -direct 'de-label'…”
Section: Risk Assessmentmentioning
confidence: 99%